An In-Vitro Study on the Influence of Ceramic Thickness in the Color of Titanium Ceramic Restoration - Limbu, Indra Kumar; Basnet, Bishal Babu (Journal of College of Medical Sciences-Nepal, 2019)
Background: Various factors such as metal alloy, thickness of the opaque porcelain, different methods of condensation of ceramic, thickness of the dentine ceramic, different ceramic firing condition affect the color of final ceramic restoration. It is not considered significant while taking single variable into account but several subtle changes in these factors lead to discernible color change. Purpose: The aim of this study was to evaluate the influence of ceramic thickness over color of ceramic layered on the titanium casting. Methods: Ultra low fusing ceramics of different thickness (0.5mm, 1mm, 1.5mm and 2mm) was veneered over a metal substrate of pure titanium and spectrophotometric analysis of 20 such discs was done to determine parameters (CIELAB system). One-way ANOVA and multiple comparison results of ANOVA were performed for statistical analysis. Results: The different thickness of ceramic significantly influences the ΔE value. There was significant change in the L* value (P<0.05) with different thickness of titanium metal ceramic tabs. There was also significant difference in C*ab values with different thickness of ceramic. Conclusions: The thickness of the ceramic has significant effect in the L* value of the titanium ceramic restoration. The thicker restoration appeared darker than the thinner one. There was also significant effect in the color saturation or chroma with different thickness of ceramic. Chroma decreased with increased thickness. Color difference between groups were significant. Overall thickness had effect on the final color of the titanium ceramic restoration.